Hands-on matrix algebra using R active and motivated learning with applications - Vinod, Hrishikesh D., author (World Scientific, 2011)
Teaches matrix algebra, allowing the student to learn the material by actually working with matrix objects in modern computer environment of R. This book provides a comprehensive overview of matrix theory without being bogged down in proofs or tedium.